Bibliometric analysis of qualitative research on patients’ experiences of intestinal stoma published between 2002 ‐ 2018 - Capilla‐Díaz, Concepción; Durán‐López, Maria I.; Martínez‐Guerrero, Juan M.; Reina‐Leal, Liliana M.; Gómez‐Urquiza, José L.; Gálvez‐González, María; Hueso‐Montoro, César (Journal of advanced nursing, 2020)
Aims The purpose of this paper was to perform a bibliometric analysis of the production of qualitative research in scientific journals through aggregation by levels and to identify factors of diversity, such as types of designs, in qualitative research on the experience of having an intestinal stoma between 2002 and 2018. Design Descriptive bibliometric study focused on the production of qualitative research on the subject of study, on three levels: micro, meso and macro. Methods Databases such as PubMed, CINAHL, Web of Knowledge, Scopus, SciELO, CUIDEN, Lilacs and Google Scholar were used to collect the data, between August ‐ November 2018. Results Nursing was the main area of knowledge. Brazil was the predominant country of origin. The most productive journal was the Journal of Wound, Ostomy & Continence Nursing. English and Portuguese were the main languages of scientific communication. The number of authors was typically between 2 and 6. Authors conducted descriptive and phenomenological studies. Conclusion The present bibliometric study helps us to map the qualitative research on the experiences of individuals with an intestinal stoma and to understand patterns in the designs, methods, disciplines and journals involved in this area of research. This will allow nurses to have a leading contribution to stoma care at their disposal. 目的本文旨在通过分级汇总对科学期刊定性研究成果进行文献计量分析,从而确定2002年到2018年期间发表的有关肠造口术后患者的定性研究中设计类型等多样性因素。设计描述性文献计量研究侧重于在微观、中观和宏观三个层面上对研究对象展开定性研究。方法通过PubMed、CINAHL、Web of Knowledge、Scopus、SciELO、CUIDEN、Lilacs和谷歌学术搜索等数据库对2018年8月至11月间发表的文献数据进行检索。结果护理是一大主要知识领域。巴西是主要来源国。最有成效的期刊为《创面、造口及自制护理杂志》。英语和葡萄牙语是科学交流的两大主要用语。作者人数通常在2到6人之间。作者还开展了描述性和现象学研究。结论当前的文献计量研究有助于我们对肠造口术后患者展开定性研究,了解这一研究领域所涉及的设计、方法、学科和期刊模式。这将使护士在造口护理方面发挥主导作用。